Pengaruh DAR, ROA, dan TATO Terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Aprilia Dwi Cahyani; Hari Setiono; Nurdiana Fitri Isnaini (CV. Kalimasada Group, 2025)
Company value is a comprehensive picture of public perception and trust in the company's performance, which is reflected through the stock price in the capital market from the inception of the company to the company's future projections. This study aims to analyze the effect of Debt to Asset Ratio (DAR), Return on Asset (ROA), and Total Asset Turnover (TATO) on Firm Value with Firm Size as a Moderating Variable. The method in this study uses a quantitative approach with multiple linear regression analysis. The research sample consisted of 21 food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2021-2024. The data used is secondary data and analyzed using IBM SPSS software. The results showed that Debt to Asset Ratio (DAR) has no effect on firm value. Conversely, Return on Asset (ROA), and Total Asset Turnover (TATO) have a significant effect on firm value. Company size is unable to moderate the relationship between Debt to Asset Ratio (DAR) and Total Asset Turnover (TATO) on firm value. Conversely, company size is able to moderate the relationship between Return on Asset (ROA) on firm value.